2007
DOI: 10.1103/physrevb.75.187402
|View full text |Cite
|
Sign up to set email alerts
|

Reply to “Comment on ‘Nature and entropy content of the ordering transitions inRCo2’ ”

Abstract: In the previous Comment, Forker and co-workers claim that perturbed angular correlation ͑PAC͒ data leave no alternative to the conclusion that the spontaneous magnetization of PrCo 2 and NdCo 2 undergoes a discontinuous, first-order phase transition at T C . We show here that their claim is in clear contradiction with a wealth of experimental evidence, including our own. Finally, we propose a possible origin for the disagreement between their interpretation of the PAC results and the literature on this subject. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 33 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…In a recent work [27], we suggested that the Banerjee criterion could be useful to discriminate the order of magnetic phase transitions in the RCo 2 series (where R is a rare earth ion). According to an extensive wealth of experimental results, the magnetic ordering transitions in RCo 2 had been always classified as first-order transitions for R = Dy, Er and Ho, and the rest as second-order transitions [28].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent work [27], we suggested that the Banerjee criterion could be useful to discriminate the order of magnetic phase transitions in the RCo 2 series (where R is a rare earth ion). According to an extensive wealth of experimental results, the magnetic ordering transitions in RCo 2 had been always classified as first-order transitions for R = Dy, Er and Ho, and the rest as second-order transitions [28].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Moreover, the large entropy change showed by ErCo 2 has led to studies on the MCE properties of the pure and pseudobinary Co Laves phases. 2,[15][16][17][18][19][20][21][22] We have also selected the ferromagnetic manganites, La 2/3 ͑Ca x Sr ͑1−x͒ ͒ 1/3 MnO 3 with x = 0, 0.5, and 1, in order to give more generality to our results. The physical properties of these materials have been reported in literature.…”
Section: Introductionmentioning
confidence: 99%
“…Forker et al [113] reported that the cubic ↔ tetragonal transition is first order, which would put it just to the first-order side of tricritical ((B * + B * ) < 0), rather than being exactly tricritical ((B * + B * ) = 0). Their conclusion is the subject of some debate, however [114][115][116].…”
Section: Appendixmentioning
confidence: 99%